Penguatan Kapasitas Pokdarwis melalui Digital Storytelling untuk Promosi Pariwisata Berbasis Komunitas di Desa Sukajadi, Bogor - Iis Mardiansyah; Rifky Maulana; Nadia Nur Soraya; Diah Tri Andini; Rosida Putri Andini (PELITA NUSA TENGGARA, 2026)
Sukajadi Village, Tamansari District, Bogor Regency, has natural and cultural potential that supports the development of community-based tourism. However, the capacity of Pokdarwis in digital literacy, content production, and governance of tourism promotions and businesses is still limited. The Community Service Program aims to increase the independence of Pokdarwis through digital storytelling to promote authentic and sustainable destinations. The methods used were a community-based participatory approach with coordination stages, field observation and FGD mapping potential-needs, workshops on the concept of Community-Based Tourism (CBT) and digital storytelling, practice photos, videos, captions (practice-based learning), assistance in strengthening promotion/branding management as well as simple business recording, implementation of content production, and evaluation-reflection. Core training activities will be held on December 4, 2025. The results showed an increase in participants' ability to formulate promotional messages based on local experiences and values, produce visual content worth uploading, and understand the importance of destination identity consistency. Concrete outputs are in the form of 10 promotional photos, 2 short videos (Reels or TikTok), 10 caption scripts, and the activation of one tourism social media account managed by Pokdarwis. In addition, the division of media managers' roles and the direction of a more structured upload strategy were formed. Partner engagement, from mapping to content production, increases the sense of belonging, confidence, and readiness to run self-promotions. Initial content assets help expand the visibility of destinations and economic opportunities for MSMEs and homestays without neglecting the ethics of cultural representation and environmental sustainability. This program emphasizes that strengthening digital narratives can be the entrance to improving governance, promotion, and developing story-based tour packages.